Incidencia del capital humano en el nivel de corrupcion: evidencia para latinoamerica, en el periodo 2000-2019. - Vaca Herrera, Tania Marisol (2022)
Corruption is a recurring phenomenon in humanity over the years, many people have taken particular benefit regardless of the social benefit, from which the poorest and most vulnerable are disproportionately affected by this scourge, the World Bank (2020) estimates that 5% of the world’s product corresponds to the cost of corruption, which corresponds to 2.5 trillion dollars. In this sense, a problem arises for economic growth and development, therefore, this research aims to evaluate the causal link between human capital and the level of corruption with evidence for Latin America during the period 2000-2019. Using the statistical sources of Transparency International (2020), Penn World Table (2019), Heritage Foundation (2020) and World Bank (2020), where a GLS model and second-generation econometric techniques are used in the presence of cross-dependence, through the Westerlund test (2007), Fully Modofied Ordinary Least Squares (FMOLS) and Granger’s causality through Dumitrecu and Hurlin (2012). Thus, the results mention a positive relationship in Latin America and in all countries classified by their income level. It should be noted that there is long-term cointegration between human capital and corruption, which means that there is a joint movement in the long term. The causality test determined that there is unidirectional, bidirectional causality and noncausality between the variables. The policy implications are aimed at strengthening the laws, through the integration of international bodies and the reform of laws that establish tougher sanctions.